THE ROLE OF ETHANOL CONSUMPTION IN ALTERING VISUAL OUTCOMES IN METHANOL-INDUCED TOXIC OPTIC NEUROPATHY: A CASE COMPARISON - I Nyoman Surya Ari Wahyudi; Vierlia, Wino Vrieda; Prayitnaningsih, Seskoati (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Methanol toxicity can cause a rapid onset of severe bilateral vision loss with prominent optic nerve head edema. This case report provides clinical manifestation of two similar acute cases of methanol induced toxic optic neuropathy with different visual outcome. The patients admitted to emergency room with weakness, headache, nausea, abdominal pain and blurred vision. Both patients drank the same bootleg alcohol 3 days before admission. The first case present worse clinical condition than the second case. Further history taking revealed the patient in second case had ingested ethanol 3 hours prior to the bootleg alcohol. Both patients were treated with hemodialysis, high dose of intravenous steroid and folic acid along with supportive therapies. Funduscopy examination and optic nerve head Ocular Coherence Tomography revealed worse edema in the first patient. On the first month follow-up, the visual acuity (VA) of the first case showed no significant improvement, while the second case revealed normal VA on both eyes. The better visual outcome in second case may caused by history of ethanol consumption which prevented more severe methanol toxicity, but further investigation may still be needed.